The Influence of Motivation and Attitudes Towards Consumer Purchase Decisions on Honda Beat Motorcycles - Buchori Buchori (International Journal of Ecma Science, 2021)
The purpose of the authors in this study is auto find out if there is the influence of motivation and attitudes on consumer purchasing decisions for Honda Beat Brand motorbikes (Case Study on Consumers in Way Jepara District). Data collection techniques used in this study were observation, interviews, questionnaires and documentation. As forThe population in this study were all Honda Beat motorbike consumers in Way Jepara District. The analysis technique in this research is multiple linear regression formula. Based on the results of the analysis obtained R value of 0.790. This means that there is a strong relationship between X1 and X2 and Y, and the R Square value is 0.624 or 62.4%. This means that changes in variable Y are influenced by variations in variables X1 and X2 of 62.4% and the rest is influenced by variables not examined in this study. Then in the Coefficients table, the sig value is obtained. From variables X1 and X2 0.05, the partial hypothesis is accepted, which means that there is an effect of X1 on Y and X2 on Y. Meanwhile, from the Anova table, the sig value is obtained. equal to 0.005 0.05, thus the proposed hypothesis is accepted. This means that there is an influence of motivation and attitude on consumer purchasing decisions for Honda Beat motorbikes (Case Study on Consumers in Way Jepara District).